Principles and practice of psychiatric nursing - 4 0 16; 1949- Stuart, Gail Wiscarz; 5 (St. Louis, Missouri : Mosby Elsevier, 2009)
Provides an overview of the principles and practices of psychiatric nursing.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; nursing.;methods. -- Psychiatric nursing.;Mental Disorders;Psychiatric Nursing;Psychiatric nursing; 20; 2